Aware of the Future? Adaptation and Refinement of the Futures Consciousness Scale - Lalot Fanny; Ahvenharju Sanna; Minkkinen Matti (Hogrefe, 2025)
Abstract.Introduction: Futures consciousness (FC) refers to the capacity that a person has for understanding, anticipating, and preparing for the future. A psychometric instrument, the FC scale, was recently developed to measure FC as an interindividual difference. However, this initial scale suffered from some shortcomings due to a few underperforming items. Objectives: In this paper, we present and validate the revised FC scale, which aims to address these shortcomings. Methods and Results: Data from a representative sample of N = 1,684 British participants demonstrated good psychometric properties of the revised scale (and better than the original) as well as good predictive validity. Specifically, individuals' scores were positively related to self-reported future-oriented behavior, such as engagement in civic collective action and general engagement in politics. The five-dimensional structure of the scale was also replicated. Conclusion: The revised FC scale proves a reliable tool that can be used by both researchers and practitioners.